Mempelajari Senyawa Mirisitrin Dengan Penambahan Substituen NH2, NO2, dan CH3 Sebagai Inhibitor Korosi Menggunakan Metode Density Fuctional Theory (DFT) - Azuxe Tullatif (Universitas Jambi, Fakultas Sains dan Teknologi, Program Studi Kimia, 2020)
Corrosion inhibition ability myricitrin compound (M1) with the addition of NH2 (M2), NO2 (M3), and CH3 (M4) on the metal surface has been studied using Fuctional Density Theory (DFT) with a base set of B3LYP / 6-31G (d, p). Parameters obtained from the optimization result are the value EHOMO, ELUMO and dipole moment. Of the value EHOMO and ELUMO obtained and calculated the value of the energy gap (AE), ionization potential (IP), electron affinity (EA), electronegativity (χ), hardness (η), softness (σ), electron transfer (ΔN), and electrophilicity (ω). Computational calculations show that the compound M4 has the best corrosion inhibition ability. Based on the value EHOMO, the energy gap (AE), ionization potential (IP), hardness (η), softness (σ) and electron transfer (ΔN). Keywords: DFT, Corrosion Inhibition, EHOMO, ELUMO